2000
DOI: 10.1046/j.1468-2982.2000.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcutaneous Sumatriptan on Plasma Growth Hormone Concentrations in Migraine Patients

Abstract: The purpose of this study was to assess the sensitivity of 5-HT1D receptors in migraine using sumatriptan as a pharmacological probe. The drug stimulates the release of growth hormone (GH) and this effect may be used to explore the function of cerebral serotonergic systems in vivo. We administered sumatriptan and placebo to 15 migraineurs and to 10 controls. Blood samples were collected -15, 0, 15, 30, 45, 60 and 90 min after injection. Placebo had no effect on hormone concentrations. Sumatriptan induced a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…The pulsatile secretion of GH from the anterior pituitary is mainly controlled by the reciprocal actions of GH‐RH and somatostatin. In patients with episodic migraine, GH secretion is normal, both in basal conditions and after stimulus 21,22 . In our study, we found that GH concentrations after GHRH administration were significantly reduced in CM‐MOH patients.…”
Section: Commentssupporting
confidence: 48%
See 1 more Smart Citation
“…The pulsatile secretion of GH from the anterior pituitary is mainly controlled by the reciprocal actions of GH‐RH and somatostatin. In patients with episodic migraine, GH secretion is normal, both in basal conditions and after stimulus 21,22 . In our study, we found that GH concentrations after GHRH administration were significantly reduced in CM‐MOH patients.…”
Section: Commentssupporting
confidence: 48%
“…In patients with episodic migraine, GH secretion is normal, both in basal conditions and after stimulus. 21,22 In our study, we found that GH concentrations after GHRH administration were significantly reduced in CM-MOH patients. The pathophysiological mechanisms of this reduced GH secretion are unknown.…”
Section: Commentssupporting
confidence: 47%
“…This is the first study to measure 5‐HT 1D receptor sensitivity in CTTH using sumatriptan, and the specificity of our findings deserve further investigation. We previously performed the same neuroendocrine tests in patients with migraine during the headache‐free period, and we found no alteration in 5‐HT 1D receptors sensitivity 18,19 . However, no data in patients with migraine during the headache attack are available.…”
Section: Discussionmentioning
confidence: 77%
“…Pinessi et al. (31) examined plasma growth hormone responses to subcutaneous sumatriptan, a 5‐HT1B/1D agonist in a mixed group of male and female subjects with migraine with and without aura and a healthy control group. Subjects with anxiety or depression were excluded and controls were matched for age, gender and stage of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%